(untitled) (Revista Ciência Agronômica, 2023)
The sugarcane has a high content of soluble carbohydrates, thereby resulting in many losses during its fermentation. Thus, it is necessary to use an additive that reduces the losses in the nutritional value of the forage during the ensiling process. The objective was to evaluate the use of common bean residue during the sugarcane ensiling process over the silage nutritional quality and fermentation characteristics. Were used 20 silos made of PVC pipes, in which the residue of crude and previously ground common bean processing (Phaseolus vulgaris L.) were added to newly chopped sugarcane in the proportions of 0; 50; 100 and 150 g kg-1 of fresh weight. A randomized design was used and the regression analysis was performed according to the level of common bean residue in silages. The losses from the ensiling process, the aerobic stability of the material, and the silage chemical composition, pH, NH3 -N and in vitro dry matter digestibility were analyzed. The inclusion of increasing levels of common bean residue until 150 g kg-1 improved the quality of silages, since there was a reduction in gaseous losses, improvement in food composition and in vitro dry matter digestibility, without impairing the silages pH. The common bean residue can be used as additive in sugarcane silage until 150 g kg-1 fresh weight for improving silage fermentation characteristics and dry matter digestibility.